Upaya Peningkatan Motivasi dan Hasil Belajar Pendidikan Agama Islam melalui Metode Inkuiri pada Siswa Kelas XI SMA Negeri 2 Genteng Kabupaten Banyuwangi Tahun Pelajaran 2017/2018 - Atiqatul Musyarofah (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2018)
This research is action research, because research is done to solve the problem of learning in class. This research also includes descriptive research, because it describes how a learning technique is applied and how desired results can be achieved. Observations are divided into two rounds, namely rounds 1 and 2, where each round is subjected to the same treatment (same activity flow) and discusses a sub subject that ends with a formative test at the end of each round. Created in three rounds is intended to improve the teaching system that has been implemented.it can be explained that by applying the method of inquiry found the average value of student achievement is 69.17 and completeness of learning reaches 61.11% or there are 22 students from 36 students have finished studying. The results show that in the first cycle of the classical students have not finished the study, students who get the value ≥ 65 only 61.11% smaller than the percentage of desired completeness of 85%. This is because students still feel new and have not understood what the teacher intended and used by applying the method of inquiry and above obtained the average value of formative test of 83.47 and of 36 students who have completed as many as 32 students and 4 students have not reached mastery learning. Then the classical learning completeness that has been achieved by 80% (including the category complete). The results of this cycle II have improved better than cycle I. The increase in learning outcomes in cycle II is influenced by the increase in the ability of teachers in applying inquiry so that students become more accustomed to learning like this so that students more easily understand the material that has been given. In this second cycle, completeness has been achieved in classical, so this research only until cycle II.